PENDAMPINGAN MANAJEMEN PROGRAM KEAGAMAAN SEBAGAI SARANA PENINGKATAN PENDIDIKAN SOSIAL DI MESJID AL-HIDAYAH CIRACAS KECAMATAN SERANG KOTA SERANG - Fidziah, Fidziah; Sucihati, Sucihati (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2024)
Religious program management assistance activities at the Al-Hidayah Ciracas Mosque, Serang District, Serang City, aim to improve social education among the congregation through effective and structured religious program management. This activity involves several stages, starting from needs analysis and planning, training and capacity building for mosque administrators, to implementing religious programs and periodic evaluations. The management and leadership training held succeeded in increasing the capacity of mosque administrators in planning and managing religious programs. Religious programs developed with a social values-based curriculum are able to increase social education and congregational participation. Monitoring and evaluation showed a significant increase in congregation participation and satisfaction with the programs being implemented. Documentation and publication of activities via social media has also succeeded in increasing transparency and congregation involvement. Mid-program evaluation helps identify obstacles faced and develop improvement plans for future program improvements. This activity has achieved its objectives well and can become a model for similar programs in other mosques